Instrumental variables estimation of a generalized correlated random coefficients model - Matthew Masten; Alexander Torgovitsky (Centre for Microdata Methods and Practice (cemmap), 2014)
We study identification and estimation of the average treatment effect in a correlated random coefficients model that allows for first stage heterogeneity and binary instruments. The model also allows for multiple endogenous variables and interactions between endogenous variables and covariates. Our identification approach is based on averaging the coefficients obtained from a collection of ordinary linear regressions that condition on different realizations of a control function. This identification strategy suggests a transparent and computationally straightforward estimator of a trimmed average treatment effect constructed as the average of kernel-weighted linear regressions. We develop this estimator and establish its Ín-consistency and asymptotic normality. Monte Carlo simulations show excellent finite-sample performance that is comparable in precision to the standard two-stage least squares estimator. We apply our results to analyze the effect of air pollution on house prices, and find substantial heterogeneity in first stage instrument effects as well as heterogeneity in treatment effects that is consistent with household sorting.
Keywords: C14; C26; C51; 330; correlated random coefficients; instrumental variables; unobserved heterogeneity; semiparametrics; hedonic models; residential sorting; valuation of clean air